Análise da produção científica brasileira sobre o estudar - Colombini, Filipe Augusto (2018)
Studying is an essential behavior for all students as it enables them to learn any subject on their own. However, based on the Behavioral Analysis, they need to learn to study. Three studies were carried out, with the following objectives: (1) to provide an overview of the Brazilian scientific production about studying; (2) describe characteristics of the Brazilian Behavioral Analysis production about studying, and; (3) describe the characteristics of the interventions aimed at teaching the study. Search words related to study behavior and selfregulation of learning were used and were inserted in the databases of SciELO and PePSIC, selecting the studies that met the inclusion criteria. In Study 1, 82 abstracts were analyzed, and the main results were the growth of publications from 2004; predominance of few research groups; small participation of the Education area; dominance of Cognitive Psychology; predominance of descriptive research; use of standardized instruments; prevalence of higher education; using the classroom as a setting. In Study 2, 11 abstracts were analyzed, and, among the results, it was observed: growth trend of the publications; predominance of few research groups; prevalence of intervention research; use of observation as data collection; reduced number of participants; use of varied environments such as setting. In Study 3, 16 articles were analyzed. Among other results, it was verified that there is a predominance of Cognitive Psychology and Behavior Analysis, using the group design; that the researcher himself was responsible for the intervention, in group format, in the classroom itself; almost all research was focused on teaching the participant to plan/organize available time, school materials and the place of study; the participants were also taught how to write and how to read, in addition how to analyze their own progress. It was discussed the need to of more conceptual and intervention research on the study, besides the integration of the interventions carried out by Cognitive Psychology and Behavior Analysis